The effect of strain virulence on Agrobacterium rhizogenes transformation efficiency in Eurycoma longifolia - Bhavani Balakrishnan; Advina Lizah Julkifle; Syarifah Shahrul Rabiah Syed Alwee; Chan Lai Keng; Sreeramanan Subramaniam (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Eurycoma longifolia, known locally as ‘Tongkat Ali’ in Malaysia, is popularly sought out as herbal remedy in many parts of South East Asia. Consequently, this has resulted in the indiscriminate collection of the taproot from the wild, leading to fears of extinction among conservationists. Agrobacterium rhizogenes is a naturally occurring soil bacterium that infects injured plants and causes a massive proliferation of roots, known as hairy roots. The objective of this study is to determine the transformation efficiency of 2 different strains of Agrobacterium rhizogenes on somatic embryos of Eurycoma longifolia using transient GUS expression as an indicator of successful transformation. Somatic embryos cultured in vitro for 4 to 5 weeks were used as explants and were pre-cultured for 2 days in full strength MS medium containing 0.5 mg/L IBA added with 1% PVP and 2mg/L DTT. The explants were transformed using Agrobacterium rhizogenes strains AR12 and AR14. GUS assay was carried out 1 week after transformation and observed. Observations indicate that AR12 is more effective in transforming somatic embryos of Eurycoma longifolia compared to AR14. Therefore, Agrobacterium rhizogenes strain AR12 is a potential candidate for the successful transformation of Eurycoma longifolia somatic embryos, leading to the induction of sustainable hairy root cultures